2017
DOI: 10.3847/1538-4357/aa5b83
|View full text |Cite
|
Sign up to set email alerts
|

Multi-fluid Modeling of Magnetosonic Wave Propagation in the Solar Chromosphere: Effects of Impact Ionization and Radiative Recombination

Abstract: In order to study chromospheric magnetosonic wave propagation including, for the first time, the effects of ionneutral interactions in the partially ionized solar chromosphere, we have developed a new multi-fluid computational modelaccounting for ionization and recombination reactions in gravitationally stratified magnetized collisional media. The two-fluid model used in our 2D numerical simulations treats neutrals as a separate fluid and considers charged species (electrons and ions) within the resistive MHD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 49 publications
0
52
0
Order By: Relevance
“…Alternatively, Maneva et al (2017) used a fully implicit scheme which has no restriction for the time-step and is generally more stable. It must be noted that despite the advantage of the stability, implicit schemes are more expensive computationally, because, generally, the matrix inversions needed in the implicit part are usually implemented by iterations, increasing the computational time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, Maneva et al (2017) used a fully implicit scheme which has no restriction for the time-step and is generally more stable. It must be noted that despite the advantage of the stability, implicit schemes are more expensive computationally, because, generally, the matrix inversions needed in the implicit part are usually implemented by iterations, increasing the computational time.…”
Section: Discussionmentioning
confidence: 99%
“…However, their realism is rather limited. Maneva et al (2017) modeled magneto-acoustic wave propagation in the solar stratified chromosphere including effects of impact ionization and radiative recombination. These authors found numerous difficulties in constructing an equilibrium model atmosphere for the wave propagation, and in interpreting the results of their simulations in comparisons to more standard, single fluid models.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work we present a novel numerical method for the simulation of laboratory and/or space plasmas, which solves for the ideal two-fluid model coupled to the purely hyperbolic full Maxwell's equations [22]. We extend the fully-implicit finite volume method for unstructured meshes proposed in [23], that has been used for the study of reactive and collisional chromospheric flows [24,25], to the ideal two-fluid plasma model. Compared to the previous two-fluid plasma finite volume schemes, our work proposes the following novelties:…”
Section: Introductionmentioning
confidence: 99%
“…The scheme developed in this work is implemented into COOLFluiD [29][30][31][32][33][34], an open-source object-oriented platform for scientific high-performance computing. The code is publicly available (https://github.com/andrealani/COOLFluiD) and is currently able to handle parallel multi-physics simulations including, in particular, complex compressible/incompressible flows in thermochemical equilibrium or nonequilibrium [35][36][37][38][39][40], and astrophysical plasmas [41][42][43]24,25] with a wide range of spatial discretization algorithms and time marching methods.…”
Section: Introductionmentioning
confidence: 99%
“…Soler et al (2013) studied Alfvén-wave propagation in partially ionized plasma while taking a generalized approach with free parameters with the lower solar atmosphere case as an example. Maneva et al (2017) and Wójcik, Murawski, and Musielak (2018) studied acoustic-wave propagation using a collisional two-fluid approach as well. Three-fluid simulations, with electrons being the third fluid, were carried out to study reconnection events in the chromosphere (Leake, Lukin, and Linton, 2013).…”
Section: Introductionmentioning
confidence: 99%